Inhaled budesonide does not prevent acute mountain sickness after rapid ascent to 4559 m. Issue 3 (10th September 2017) - Berger, Marc Moritz; Macholz, Franziska; Sareban, Mahdi; Schmidt, Peter; Fried, Sebastian; Dankl, Daniel; Niebauer, Josef; Bärtsch, Peter; Mairbäurl, Heimo
Recent studies showed that inhaled budesonide (200 µg twice per day) reduced the incidence of acute mountain sickness (AMS) after passive ascent to 3700 and 3900 m [1, 2]. These findings raised the possibility that mediators released from the hypoxic lung transmit signals to the brain which contribute to the cerebral processes leading to AMS [3]. Because neither of these studies reflect alpine-style climbing, the present study was performed to test whether inhalation of budesonide at two different doses (200 and 800 µg twice per day) prior to active and rapid ascent (<20 h) to 4559 m prevents AMS in this high-risk setting. Prophylactic inhalation of budesonide does not prevent acute mountain sickness after rapid ascent to high-altitude http://ow.ly/Bc9p30dOz46